Effect of Cinnamaldehyde and Citral Combination on Transcriptional Profile, Growth, Oxidative Damage and Patulin Biosynthesis of Penicillium expansum - Wang, Yuan; Feng, Kewei; Yang, Haihua; Zhang, Zhiwei; Yuan, Yahong; Yue, Tianli (Frontiers in Microbiology, 2018)
Penicillium expansum, as a main postharvest pathogen of fruits, can secrete patulin (PAT), causing fruit decay and health problems. In this study, the antifungal test, SEM (scanning electron microscope) observation, transcriptional profile, PAT biosynthesis, and physiological characters of P. expansum exposed to cinnamaldehyde and citral combination (Cin/Cit) were evaluated. Cin/Cit could inhibit the mycelial growth and spore germination of P. expansum in a dose-dependent manner. Besides, Cin/Cit caused spores and mycelia wrinkled and depressed by SEM observation. Gene expression profiles of P. expansum were conducted by RNA sequencing (RNA-seq) in the presence or absence of Cin/Cit treatment. A total of 1713 differentially expressed genes (DEGs) were obtained, including 793 down-regulated and 920 up-regulated genes. Most of the DEGs participated in the biosynthesis of secondary metabolites, amino acid metabolism, and oxidation−reduction process, etc. Cin/Cit induced the dysfunction of the mitochondrial membrane, causing the potential influence on energy metabolism and reactive oxidative species production. The changes of superoxide dismutase (SOD) and catalase (CAT) activities combing with the increase of hydrogen peroxide content indicated the oxidative stress on P. expansum induced by Cin/Cit, which corresponded well with the transcriptional results. Moreover, both the RNA-seq data and the qRT-PCR showed the remarkable down-regulation of genes included in the PAT biosynthetic pathway under the Cin/Cit treatment. These findings provided more useful information about the antifungal mechanism of Cin/Cit against P. expansum at molecular and gene levels and suggested that Cin/Cit is a potential candidate to control P. expansum.